2004
DOI: 10.1179/oeh.2004.10.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Banned in Argentina

Abstract: In 1997, Argentina gave priority to asbestos in its National Plan for the Sound Management of Chemicals, and it was the subject of a Technical Task Force on Occupational Cancer. After five years of public hearings in which government, workers, industry advocates, environmentalists, clinicians, scientists, and consumers participated, it was agreed that asbestos exposure is a risk factor for both workers and the general population, and that Argentina should provide to its people the same protections adopted by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Reviewing asbestos and mesothelioma publications from LA countries, we found several descriptive case series studies [707172737475767778]. Few studies presented mesothelioma mortality estimates for the region, presumably because data to all LA countries were unavailable, unreported, or limited in quality and coverage.…”
Section: Epidemiological Studies On Mesothelioma In Latin Americamentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewing asbestos and mesothelioma publications from LA countries, we found several descriptive case series studies [707172737475767778]. Few studies presented mesothelioma mortality estimates for the region, presumably because data to all LA countries were unavailable, unreported, or limited in quality and coverage.…”
Section: Epidemiological Studies On Mesothelioma In Latin Americamentioning
confidence: 99%
“…After decades of heavy asbestos use, Argentina instituted a national ban in 2001 [72]. Using WHO data, Park et al [83], reported that from 1994 to 2008, a total of 1,065 mesothelioma deaths were registered in Argentina – 97 per year in average.…”
Section: Epidemiological Studies On Mesothelioma In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…In Argentina most asbestiform minerals are associated with metamorphosed and/or metasomatized mafic and ultramafic igneous rocks, mainly serpentinites and amphi bolic rocks, talc and vermiculite deposits as well as with dolomitic rocks (Angelelli et al 1980;Locati et al 2014;Lescano et al 2016a). Their production started in 1920, stimulated by the industrial use of asbestos in postwar years, but they have been banned since 2003 (Rodriguez 2004). However, asbestos research is still important in Argentina because many active mines and future projects can poten tially incorporate asbestiform fibers during the exploitation works (e.g., serpentinite, talc, vermiculite and carbonate deposits).…”
Section: Introductionmentioning
confidence: 99%
“…Sepiolite is a naturally occurring phyllosilicate, of fibrous habit, whose structure consists of channels running parallel to the fibres, called zeolitic channels, which are responsible for most of its properties, among them its absorbing capacity (Jones and Galán 1988). The morphology of sepiolite has sparked scientific debate due to its toxicity and it may be included in the asbestos group in future regulatory legislation (Rodríguez 2004).…”
Section: Introductionmentioning
confidence: 99%